Demotic Papyrus Hamburg 39 (inv. no. 35.2806): A New Religious Text from Roman Egypt - La’da, Csaba (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
This article offers the first edition of a Demotic papyrus fragment of early Roman date and of uncertain, probably Fayumic, provenance in the collection of the Hamburg State and University Library Carl von Ossietzky. The fragment preserves parts of two columns of a hitherto unattested enigmatic religious work, for which mostly only distant and short parallels can be found in the evidence currently available to us in any of the Egyptian languages and scripts used in the Late and Graeco-Roman Periods. The only relatively close parallel that we are aware of is a slightly modified form of a sentence that occurs in the composition known as ‘The Great Decree Issued to the Nome of the Silent Land’. The vocabulary and the meagre parallels suggest that we may be catching a glimpse of a previously unknown work of Osirian religious literature. This article provides a general introduction, a transcription and translation of the text, as well as a commentary.